2020
DOI: 10.1021/acs.jpclett.0c02272
|View full text |Cite
|
Sign up to set email alerts
|

Bond-Breaking/Bond-Forming Reactions by Vibrational Excitation: Infrared-Induced Bidirectional Tautomerization of Matrix-Isolated Thiotropolone

Abstract: Infrared vibrational excitation is a promising approach for gaining exceptional control of chemical reactions, in ways that cannot be attained via thermal or electronic excitation. Here, we report an unprecedented example of a bond-breaking/bond-forming reaction by vibrational excitation under matrix isolation conditions. Thiotropolone monomers were isolated in cryogenic argon matrices and characterized by infrared spectroscopy and vibrational computations (harmonic and anharmonic). Narrowband near-infrared ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 63 publications
(84 reference statements)
3
40
0
Order By: Relevance
“…For ease of identification, we computed anharmonic IR spectra of 1 and 2 at B3LYP/6–311++G(3df,3pd). DFT in conjunction with a large Pople basis set generally reproduces matrix IR spectra very reasonably; recent precedence is provided in a study on thiotropolone [49] . Herein, the inclusion of anharmonicities leads to an overall good agreement between computations and measurements (see Supporting Information for details).…”
Section: Resultsmentioning
confidence: 79%
“…For ease of identification, we computed anharmonic IR spectra of 1 and 2 at B3LYP/6–311++G(3df,3pd). DFT in conjunction with a large Pople basis set generally reproduces matrix IR spectra very reasonably; recent precedence is provided in a study on thiotropolone [49] . Herein, the inclusion of anharmonicities leads to an overall good agreement between computations and measurements (see Supporting Information for details).…”
Section: Resultsmentioning
confidence: 79%
“…Matrix isolation has also many practical advantages compared with other possible approaches (e.g., molecular beams), in particular when the probing method is a spectroscopic technique [ 31 , 32 ]. Moreover, the concerted use of matrix isolation infrared spectroscopy and quantum chemical electronic structure calculations has been proven to be a very powerful tool for structural studies on conformationally flexible and multi-isomeric complex systems [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of intramolecular hydrogen-atom transfer induced by excitation of higher vibrational states of the ground electronic state has recently been experimentally proven. 52 It was demonstrated that near-IR excitation of thiotropolone leads to the transformation of the thio-hydroxy tautomer into the oxo-thiol tautomeric form. This transformation occurs by a hydrogen-atom shift from the oxygen atom to the vicinal sulfur atom of the thiotropolone molecule.…”
Section: Discussionmentioning
confidence: 99%
“…This transformation occurs by a hydrogen-atom shift from the oxygen atom to the vicinal sulfur atom of the thiotropolone molecule. 52 This mechanism may be operative especially for cases where the energy barriers for tautomerization in the ground electronic state are relatively low. For molecules, where the tautomers are separated by very high barriers, the PIDA mechanism involving dissociation of a hydrogen atom, followed by its association with another heteroatom, seems to be more adequate.…”
Section: Discussionmentioning
confidence: 99%